Floral Scents of a Deceptive Plant Are Hyperdiverse and Under Population-Specific Phenotypic Selection - Gfrerer, Eva; Laina, Danae; Gibernau, Marc; Fuchs, Roman; Happ, Martin; Tolasch, Till; Trutschnig, Wolfgang; Hörger, Anja C.; Comes, Hans Peter; Dötterl, Stefan (Frontiers in Plant Science, 2021)
Floral scent is a key mediator in plant–pollinator interactions; however, little is known to what extent intraspecific scent variation is shaped by phenotypic selection, with no information yet in deceptive plants. We collected inflorescence scent and fruit set of the deceptive moth fly-pollinated Arum maculatum (Araceae) from six populations north vs. five populations south of the Alps (233 individuals in total), and tested for differences in scent, fruit set, and phenotypic selection on scent across this geographic barrier. We recorded 289 scent compounds, the highest number so far reported in a single plant species. Most of the compounds occurred both north and south of the Alps; however, plants of the different regions emitted different absolute and relative amounts of scent. Fruit set was higher north then south of the Alps and some, but not all differences in scent could be explained by differential phenotypic selection in northern vs. southern populations. Our study is the first to provide evidence that floral scents of a deceptive plant are under phenotypic selection and that phenotypic selection is involved in shaping geographic patterns of floral scent in such plants. The hyperdiverse scent of A. maculatum might result from the plant’s imitation of various brood substrates of its pollinators.